Master Planning for Conservation and Development of Krung Rattanakosin 2032 - Peerapun, Wannasilpa; Sereerat, Sirirat; Sanit, Peamsook; Vichienpradit, Pornsan; Wi-te, Yuwadee (Nakhara : Journal of Environmental Design and Planning, 2020)
Master Plan of Conservation and Development of Krung Rattanakosin 2032 has planned under the vision of "A glorious capital city of Siam Kingdom, dignified by urban heritages, blending with multi-identical-cultural dimensions of the local community, and the contemporary urbanism." An integrated planning in responsive with the dynamic contexts under the combining the conservation and development into one framework. Highlighted on the Krung Rattanakosin urban structure and significant cultural heritages which express the important stories of the area, including the story of the two capital cities of Thonburi and Krung Rattanakosin, the stories about palaces, and spatial development.